2009
DOI: 10.2320/matertrans.m2009245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Hydroxyapatite Binders on Morphology, Ca/P Ratio and Hardness of Nd-YAG Laser Clad Coatings

Abstract: Hydroxyapatite (HA) is a well known biocompatible coating material used to improve the bonding quality between metallic substrates and the surrounding bone tissue following implantation. In this study, HA is mixed with two different binders, namely water glass (WG) and polyvinyl alcohol (PVA), respectively, and is then clad on Ti-6Al-4V substrates using an Nd:YAG laser beam. The results show that for both binders, the weld surface width, penetration depth and heat affected zone decrease with an increasing trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…8 Cross-sectional hardness profiles of FA/Al 2 O 3 specimenstechnique used and the parameter settings applied. For example, recent studies have shown that their hardness may range from 260 to 1000 HV[21,[37][38][39]. The results obtained in this study have shown that the addition of Al 2 O 3 to FA yields a hardness value of up to 1300 HV.…”
supporting
confidence: 48%
“…8 Cross-sectional hardness profiles of FA/Al 2 O 3 specimenstechnique used and the parameter settings applied. For example, recent studies have shown that their hardness may range from 260 to 1000 HV[21,[37][38][39]. The results obtained in this study have shown that the addition of Al 2 O 3 to FA yields a hardness value of up to 1300 HV.…”
supporting
confidence: 48%
“…The slow degradation of the β-TCP coating occurred in the course of bone remodelling without loss of fixation, and osteoclasts probably played a major role. Degraded β-TCP at the interface likely induced the formation of new bone (Tanimoto and Nishiyama, 2008, Chien et al, 2009). Slow coating resorption and bone remodelling have resulted in an extent of bone-implant osseointegration.…”
Section: Resultsmentioning
confidence: 99%
“…The slow release of HA ions at the interface probably stimulates the formation of new bones. 38,39 An extended osseointegration will result from slow resorption of implant coating and bone remodeling. Coated Ti dental implants will be covered with three-layered cell sheets that successfully form using collagen grafts as a scaffold 40 to construct biohybrid implants.…”
Section: Discussionmentioning
confidence: 99%